Crucial Cell Signaling Compounds Crosstalk and Integrative Multi-Omics Techniques for Salinity Stress Tolerance in Plants - Singhal, Rajesh K.; Saha, Debanjana; Skalicky, Milan; Mishra, Udit N.; Chauhan, Jyoti; Behera, Laxmi P.; Lenka, Devidutta; Chand, Subhash; Kumar, Vivek; Dey, Prajjal; Indu,; Pandey, Saurabh; et al. (Frontiers in Plant Science, 2021)
In the present climatic change scenario, abiotic stresses are the primary cause for yield gap in major agricultural crops. Among them, salinity is considered as calamitous stress for its globally distribution and high magnitude. Salinity affects the plant processes and growth as; imposing of osmotic stress and destroys the ionic, redox, signalling and phytohormones homeostasis, which causes for oxidative stress and ultimately imbalances the metabolic activities. In this consequences, signaling compounds crosstalk such as gasotransmitters (nitric oxide (NO), hydrogen sulfide (H2S), hydrogen peroxide (H2O2), calcium (Ca), reactive oxygen species (ROS) and plant growth regulators (auxin, ethylene, abscisic acid, salicylic acid) have decisive role in regulating plant stress signaling and administer the unfavorable circumstances including salinity stress. Moreover, recent significant progress has been made with the use of omics techniques (transcriptomics, genomics, proteomics, and metabolomics) to reinforce the deep understanding of molecular insight in multiple stresses tolerance. Although, there is very little information on gasotransmitters and plant growth regulators crosstalk and inadequacy of information regarding the integration of multi-omics technology during salinity stress. Therefore, there is urgent need to understand the crucial cell signalling crosstalk mechanisms and integrative multi-omics techniques to provide a more direct approach for salinity stress tolerance. To address the mentioned words, this review covers the common mechanism of signalling compounds and role of different signalling compounds crosstalk under salinity stress tolerance. Thereafter, we mentions the integration of different omics technology and compile the recent information in respect to salinity stress tolerance.